We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.


Questions 70
Answers 574


Hi there,


there's lot's of answers to your question, but I think you're just looking for an example of a fraction that is in between these two.


Let me give you some help here. Suppose I have 1 pizza and I cut it in 4 equal slices then if I take 1 slice I'll have 1/4 pizza. However if I cut the pizza in 8 slices and take 2 slices I'll still have 1/4 pizza.


Now suppose I have 1 pizza and I cut it in 11 equal slices then if I take 1 slice I'll have 1/11 pizza. However if I cut the pizza in 22 slices and take 2 I'll still have 1/11 pizza. Therefore we can say 1/11 = 2/22.


With similar reasoning we can also say that 1/12 = 2/24 (try to think of this pizza experiment yourself.)


So the question 1/11<...<1/12 is actually the same question as  2/22<...<2/24.


Now, I can divide a pizza in 22 slices, I can divide a pizza in 24 slices, but I could also divide it in 23 slices (Don't ask me to actually do it though, it would be very cumbersome).


Now if I have 2 slices of the pizza that is cut in 22 pieces those pieces will be bigger than 2 slices of the pizza that is cut in 23 pieces and those will again be bigger than the 2 slices of the pizza that is cut in 24 pieces.


Therefore we can state 2/22<2/23<2/24.


Now remember that we found that 1/11=2/22 and 1/12=2/24.


Hence we can also write 1/11<2/23<1/12.


And there you have an answer to your question, note however that it is not the only answer.


Suppose I cut the pizza in 44 slices and take 4 for myself I'd also have 1/11th pizza. 


Similarly as above we can therefore also reason that 4/44<4/45<4/46<4/47<4/48 and therefore that


1/11<4/45<4/46<4/47<1/12 (try to follow the reasoning above and do this for yourself.)



I hope this helped cool


Sep 7, 2015

Let's first take a look at what happens in the first years.

Emily starts out with a salary of $25,000

After one year her salary has increased with 6%.

This means her salary is 106% of what it was last year.

Therefore her salary is now

$$(\frac{106}{100})\times\$25,000 = 1.06 \times\$25,000 = \$26,500$$

One year later her salary again increases with 6%

The means her salary is again 106% of what it was last year

Therefore her salary is now 

$$(\frac{106}{100})\times\$26,500 = 1.06 \times \$26,500 = \$28,090$$


Now suppose we had the same situation and we wanted to know what her salary was after 2 years.

Instead of first calculating her salary after one year we could also have immediately calculated

$$(\text{salary after two years}) = 1.06 \times (\text{salary after one year}) = 1.06 \times 1.06 \times (\text{starting salary}) = (1.06)^2 \times(\text{starting salary}) = (1.06)^2 \times \$25,000 = \$28,090$$


Similarly, we could show that for 3 years we have that 

$$(\text{salary after three years}) = 1.06^3 (\text{starting salary}) = 1.06^3 \times \$25,000$$

and that for x years we have that

$$(\text{salary after x years}) = 1.06^x = (\text{starting salary})$$


Now, if we rewrite the exercise as an equation we need to solve

$$1.06^x \times \$25,000 = 2 \times \$25,000$$

dividing both sides by 25000 gives us

$$1.06^x = 2$$


Now, I'm not sure what your level is so I'll give you two options

option 1 (the easy option (for whole years)):

Start with 1 and keep multiplying by 1.06 until the value is bigger or equal to 2.

The number of times you multiplied is the value of x.

To illustrate, this gives

1*1.06 = 1.06\\
1*1.06*1.06 = 1.06^2 = 1.1236\\
1*1.06*1.06*1.06 = 1.06^3 = 1.191016\\
1.06^{11} = 1.898298558\\
1.06^{12} = 2.012196472\\

Hence after 12 years, her income has doubled.


Option 2 (the advanced option (for partial years)):

This option makes use of logarithms. If you've never heard of logarithms, this method is not for you.


We indicate the natural logarithm as $$ln() = {}^elog()$$

We have that

1.06^x = 2\\
e^{ln(1.06^x)} = 2\\
e^{x \times ln(1.06)} = 2\\
x \times ln(1.06) = ln(2)\\
x = \frac{ln(2)}{ln(1.06)} \approx 11.8957

 Hence the answer is approximately 11.8957 years


Apr 8, 2015